2001
DOI: 10.1289/ehp.01109669
|View full text |Cite
|
Sign up to set email alerts
|

Endosulfan exposure disrupts pheromonal systems in the red-spotted newt: a mechanism for subtle effects of environmental chemicals.

Abstract: Because chemicals introduced into the environment by humans can affect both long-term survivorship and reproduction of amphibians, discovering the specific mechanisms through which these chemicals act may facilitate the development of plans for amphibian conservation. We investigated the amphibian pheromonal system as a potential target of common environmental chemicals. By treating female red-spotted newts, Notophthalmus viridescens, to a commonly used insecticide, endosulfan, we found that the pheromonal sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 31 publications
2
42
0
2
Order By: Relevance
“…Those authors found a 50 and 70% decrease in EOG 30 min following a exposure at 1 and 10 g/L, respectively; we noted a decrease of 30 and 45%, respectively, for the same concentrations. 25,2006 K.B. If the difference is caused by the greater stimulus concentration, this suggests that EOG alteration, as assayed through EOG peak size, may be-Environ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those authors found a 50 and 70% decrease in EOG 30 min following a exposure at 1 and 10 g/L, respectively; we noted a decrease of 30 and 45%, respectively, for the same concentrations. 25,2006 K.B. If the difference is caused by the greater stimulus concentration, this suggests that EOG alteration, as assayed through EOG peak size, may be-Environ.…”
Section: Discussionmentioning
confidence: 99%
“…For glyphosate, the median inhibitory concentration (IC50) was determined for each exposure time (2,5,10,15,20,25, and 30 min) by fitting curves to EOG inhibition versus glyphosate concentration and interpolating 50% EOG reduction. For the curves, given the small number of points (average values for control, 0.1, 1, 10, and 100 mg/L at each time point), a three-parameter exponential decay model (inhibition ϭ y o ϩ a·e b [glyphosate] ) was used for simplicity, because a polynomial model did not provide a better fit.…”
Section: Statisticsmentioning
confidence: 99%
“…These results suggest a high specificity of atrazine and Cd in the bullfrog steroidogenic cells. Another study [37] reported that the pheromonal system of the red-spotted newt, Notophalmus viridescens, was highly susceptible to low-concentration exposure to endosulfan. The least endocrine-specific toxicant, compared with Cd and atrazine, was endosulfan with a LC50:EC50 ratio of 3.05 for X. laevis.…”
Section: Discussionmentioning
confidence: 99%
“…Several exciting studies have expanded our understanding of systems capable of endocrine disruption, such as the studies documenting contaminant-induced disruption of the interspecies signaling system associated with the nitrogen fixation pathway (Fox et al 2001), thyroid hormone–dependent gene expression during metamorphosis in amphibians (Crump et al 2002) or pheromonal communication among salamanders (Park et al 2001; Park and Propper 2002). These examples are just a few of the natural systems that require further research efforts.…”
Section: Novel Mechanisms Of Endocrine Disruptionmentioning
confidence: 99%